2021
DOI: 10.12659/msm.932370
|View full text |Cite
|
Sign up to set email alerts
|

Identification of m6A-Related Biomarkers Associated with Prognosis of Colorectal Cancer

Abstract: Background Colorectal cancer (CRC) is the second most deadly cancer in the world according to GLOBOCAN 2020 data. Accumulating evidence suggests that RNA methylation modification is also misregulated in human cancers and may be a potential ideal target for cancer treatment. Material/Methods m6A-related differentially expressed genes (DEGs) were identified from colon adenocarcinoma and rectum adenocarcinoma esophageal carcinoma patients with different pathological stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…24 UBE2H was identified as a m6A-related hub gene closely related to the clinicopathology and prognosis of CRC using a prognostic signature model. 25 In concordance with our findings, Cejas et al also found that CNOT3 overexpression in colon tissues was associated with worse prognosis outcomes of CRC. 26 Our study firstly developed a prognostic risk score based on 18 m6A-related gene expression signatures that could be used as an index to predict the OS of CRC patients, and further validated its predictive performance in two independent external datasets.…”
Section: Discussionsupporting
confidence: 93%
“…24 UBE2H was identified as a m6A-related hub gene closely related to the clinicopathology and prognosis of CRC using a prognostic signature model. 25 In concordance with our findings, Cejas et al also found that CNOT3 overexpression in colon tissues was associated with worse prognosis outcomes of CRC. 26 Our study firstly developed a prognostic risk score based on 18 m6A-related gene expression signatures that could be used as an index to predict the OS of CRC patients, and further validated its predictive performance in two independent external datasets.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, the use of bioinformatics methods to explore differentially expressed genes has made significant progress in pancreatic cancer ( Xu et al, 2020 ), gastric cancer ( Cheng et al, 2020 ; Gu et al, 2021 ; Yuan et al, 2021 ), colorectal cancer ( Cheng et al, 2021 ; Zhang and Zhang, 2021 ), prostate cancer ( Rode et al, 2021 ) and other diseases ( Ao et al, 2021 ; Yu et al, 2021b ; Laudisi et al, 2021 ; Zhang et al, 2021 ; Zhao et al, 2021 ). The occurrence and development of breast cancer is a process involving and synergistic action of multiple genes in multiple stages ( Kretschmer et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant m 6 A modifications are closely related to the onset and progression of various cancers, including CRC ( Liu et al, 2018 ; Gong et al, 2019 ; Wang et al, 2020 ; Wang et al, 2021 ; Zhang and Zhang., 2021 ). Nowadays, lncRNAs are reported to act essential roles in the development of tumors, especially in epigenetic regulation, protein interaction, and RNA metabolism.…”
Section: Discussionmentioning
confidence: 99%